PENGARUH MANAJEMEN TENAGA PENDIDIK DAN KEPENDIDIKAN TERHADAP MUTU PENDIDIKAN DI MTS K.H A WAHAB MUHSIN SUKAHIDENG KABUPATEN TASIKMALAYA - Fauzi, M Ridwan; Komalasari, Imas; Abdussalam, Aam (An-Nahdliyyah: Jurnal Studi Keislaman, 2024)
Teaching and education staff management must be implemented as optimally as possible because it will have an impact on the quality of education, such as implementation of educational administration well. The aim of this research is to find out: the management of teaching and educational staff, quality of education, and the magnitude of the influence of the administration of teaching and education staff on improving the quality of education at MTs. K.H A Wahab Muhsin Sukahideng Tasikmalaya Regency. Management of teaching and educational staff consist of planning, recruitment and placement, coaching and development, performance assessment, compensation and dismissal. Meanwhile, the quality of education consists of parental support, quality of education, student commitment, school leadership, quality of learning, resource management at school and school comfort. The research method used was a survey method with a quantitative approach using 54 respondents. Data collection techniques use documentation, questionnaires, interviews and observation. Data analysis uses validity tests, reliability tests, correlation, regression, coefficient of determination and non-determination coefficient. The results of the research show that the management of teaching and educational staff (X) is in the very good category with a mean of 4.379 and the quality of education (Y) is in the very good category with a mean of 4.360. The correlation result of the management of teaching and educational staff on the quality of education is 0.377, which is in the low category. . The regression results of the management of teaching staff and education on the quality of education is 0.377, which is greater than the rtable 0.279 and the significance level is 0.005. This means that there is a positive and significant influence between the management of teaching staff and education (X) and the quality of education (Y). Meanwhile, the calculation result of the coefficient of determination is 14% for the quality of education. 86% is influenced by other variables not examined in this research.